2015
DOI: 10.1177/0117196815594718
|View full text |Cite
|
Sign up to set email alerts
|

Immigrant–native fertility differentials: The Afghans in Iran

Abstract: International migration is increasingly important in shaping national population dynamics, both directly through adding or subtracting people, and indirectly, through the fertility of immigrants. International migrants rarely share the fertility characteristics of either origin or destination populations. However, the relationship between migration and fertility is little understood, especially that relating to refugee populations. This study examined the fertility differentials of one of the world’s largest r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…Afghan women and men have indicated that they are actively embracing new opportunities available within Australia, and making informed, autonomous decisions about family size that contrast with norms of Afghanistan; a finding consistent with prior migrant research in Iran (Abbasi-Shavazi et al 2015). However, this study has presented new insights into challenges and transcultural tensions that also influence decisions to have fewer children.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…Afghan women and men have indicated that they are actively embracing new opportunities available within Australia, and making informed, autonomous decisions about family size that contrast with norms of Afghanistan; a finding consistent with prior migrant research in Iran (Abbasi-Shavazi et al 2015). However, this study has presented new insights into challenges and transcultural tensions that also influence decisions to have fewer children.…”
Section: Discussionsupporting
confidence: 82%
“…While migration is a significant life event that can profoundly impact sexual and reproductive health (Ellawela et al 2017), there is a paucity of research that has considered the ways that rapid social and cultural change influences family planning in refugee and migrant populations. The limited research in this area has found that some cultural groups, such as Somali and Afghan migrants, have experienced a reduction in family size following resettlement in countries with lower fertility rates (Abbasi-Shavazi et al 2015;Dengi, Koivusilta, and Ojanlatva 2006). Additionally, several studies have highlighted shifts in knowledge, attitudes and behaviours by undertaking intergenerational comparisons (Dean et al 2017;Rogers and Earnest 2014).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Large-scale forced migration from Afghanistan to Iran began with first the Marxist coup d'état in Kabul in 1978, followed by the Soviet invasion of Afghanistan in 1979. Approximately three million Afghan refugees had arrived in Iran by 1989 (Abbasi-Shavazi et al, 2015). In the 1990s, a new wave of Afghan refugees began arriving primarily to escape the rule of the Taliban, some of whom returned after the fall of the Taliban in 2001.…”
Section: The History Of Afghan Migration To Iranmentioning
confidence: 99%
“…Although migration and fertility are examined in low-and middle-income countries, these analyses focus on domestic migrants (e.g., Chattopadhyay et al 2006;Hervitz 1985;Liang et al 2014;Rokicki et al 2014;Werwath 2011); the impact of remittances upon origin community fertility (Anwar and Mughal 2016); the ways that male outmigration shapes fertility in source communities (Agadjanian et al 2011;Clifford 2009;White and Potter 2013); and the diffusion of fertility ideation into sending societies (Lerch 2015;Bertoli and Marchetta 2015;Beine et al 2013;White and Buckley 2011). While a small number of recent studies begin to address fertility and migration between low-and middle-income countries (e.g., Abbasi-Shavazi et al 2015), questions regarding immigrant childbearing in South-South migrations relative to South-North migrations remain unanswered.…”
Section: Literature Reviewmentioning
confidence: 99%